ETHICAL AND LEGAL ASPECTS OF DICTIONARIES IN ENGLISH LANGUAGE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article "Ethical and Legal Aspects of Dictionaries in EnglishLexicography" delves into the complex challenges faced by lexicographers in the digitaland multicultural era. It examines ethical responsibilities such as inclusivity, fairness, andunbiased representation of diverse linguistic and cultural communities, alongsidecontentious issues like the inclusion of offensive or controversial terms. The legaldimensions are explored in the context of copyright protection, intellectual property rights, trademarks, and the rise of digital and user-generated dictionaries. The paper highlights theevolving role of artificial intelligence and corpus linguistics in addressing these issueswhile proposing best practices for ethical lexicography and robust legal frameworks. Thearticle serves as a vital reference for understanding the intersection of linguisticscholarship, societal values, and legal constraints in